Are Voters Rationally Ignorant? An Empirical Study for Portuguese Local Elections - José da Silva Costa; Ester Gomes Silva (European Regional Science Association (ERSA), 2004)
The application of the rational choice postulate to a political context invariably leads to the conclusion that most voters are ill informed when making the decision for whom to vote. In this paper, the authors do an empirical evaluation of the rational ignorance theory, based on the results of the 1997 Portuguese Local Elections. The results only partially sustain the hypothesis of rational ignorance, although it is also possible to identify several limitations that prevent the establishment of definite conclusions in this specific field.JEL Classification: H7 Key words: Voter's Behaviour; Local Elections; Local Governments; Portugal.
Keywords: H7; 330; Voter's Behaviour; Local Elections; Local Governments; Portugal